Cracks in the pattern: Gallagher’s theory of the self and the dynamics of schizophrenic selfhood - Fazakas, István; Fuchs, Thomas; Thoma, Samuel; Bois, Cassandre; Gozé, Tudi (Frontiers in Psychiatry, 2025)
The contemporary debate on selfhood in philosophy, psychiatry, and cognitive science unfolds most often between two opposing tendencies: reductionism, seeking to identify a fundamental and minimal core of selfhood, and eliminativism, denying the existence of the self. Shaun Gallagher’s Pattern Theory of the Self (PTS) has emerged as a promising alternative approach. By defining the self as a dynamical gestalt composed of heterogeneous elements and a multiplicity of interacting processes—including embodied, affective, cognitive, narrative, and social dimensions—the PTS offers an integrative and pluralist account of the self. Nevertheless, while the PTS succeeds in avoiding essentialism and supporting pluralism it faces the challenge of providing concrete tools to analyze the organization of self-patterns, particularly in pathological cases such as schizophrenia. We propose a reframing of PTS through the concept of architectonics, rooted in Kantian philosophy and developed in the phenomenological tradition. The architectonic view allows for a stratified and genetic account of self-patterns, attentive to the polyrhythmic unfolding of lived experience across multiple temporal and structural layers. Furthermore, it enables a fine-grained analysis of pathologies and recovery of the self, notably in schizophrenia spectrum disorders, where selfhood appears to be fractured.